Ferroptosis in COVID-19-related liver injury: A potential mechanism and therapeutic target - Chen, Yunqing; Xu, Yan; Zhang, Kan; Shen, Liang; Deng, Min (Frontiers in Cellular and Infection Microbiology, 2022)
The outbreak of COVID-19, which is caused by severe acute respiratory syndrome coronavirus 2(SARS-CoV-2), has spread worldwide and caused dramatic threaten of global public health. SARS-CoV-2 infection not only influence the respiratory system, but also lead to hepatic injury. Ferroptosis is a distinct iron-dependent form of non-apoptotic cell death, which has been investigated in various pathological conditions, such as cancer, ischemia/reperfusion injury as well as liver diseases. To date, whether ferroptosis take part in the pathophysiological process of COVID-19-related liver injury has not been elaborated. This review describes the pathological changes in COVID-19-related liver injury and speculates ferroptosis as a potential mechanism in COVID-19-related hepatic injury. Furthermore, we discuss ferroptosis might be a therapeutic target for COVID-19-related liver injury. Discoveries in these areas will improve our understanding for strategies to prevent and treat hepatic injury caused by COVID-19.